Myocardial infarction under the age of 36: prevalence of thrombophilic disorders - Rallidis, Loukianos S.; Belesi, Chrusula I.; Manioudaki, Helen S.; Chatziioakimidis, Vassilis K.; Fakitsa, Vassiliki C.; Sinos, Loukas E.; Laoutaris, Nikolaos P.; Apostolou, Thomas S. (Thrombosis and Haemostasis, 2003)
It has been suggested that thrombotic tendency increases the risk of myocardial infarction (MI). To investigate the association between the risk of MI at a young age and genetic thrombogenic disorders (G20210A mutation in the prothrombin gene, G1691A mutation in the factor V gene and deficiencies of protein C, protein S and antithrombin III) we conducted a case-control study among 70 survivors of MI who had experienced the event before the age of 36 and 260 healthy subjects. The G20210A mutation in the prothrombin gene was found more often in young patients with MI than among controls (11.4 versus 3.1%). The odds ratio (OR) for MI for carriers versus non-carriers was 4 (95% confidence interval [CI], 1.5 to 11.3). The adjusted OR for major cardiovascular risk factors (smoking, hypecholesterolaemia, diabetes mellitus, hypertension and obesity) was 4.3 (95% CI,1.3 to 14). The simultaneous presence of both G20210A mutation in the prothrombin gene and smoking further increased the risk of MI compared with nonsmokers and non-carriers (OR, 58; 95% CI, 11.4-294). The G1691A mutation in factor V gene was not associated with an increased relative risk for MI (OR, 0.87; 95% CI, 0.26 to 2.5). Finally, there was no significant difference in the prevalence of deficiencies of protein C, protein S and antithrombin III between cases and controls. In conclusion, our data indicate that the G20210A mutation in the prothrombin gene was the only genetic prothrombotic risk factor associated with the risk of developing MI under the age of 36 years.
Keywords: Factor V Leiden mutation; premature myocardial infarction; pro-thrombin gene mutation; thrombophilic disorders